Coronary stent technology and the role of inflammation in the atherogenesis: problems and prospects - V. V. Ryabov; E. I. Kretov; S. V. Popov; I. Sh. Khassanov; M. Yu. Yakovlev (Бюллетень сибирской медицины, 2021)
Coronary artery disease (CAD) remains one of the leading causes of death in developed industrial countries. Timely and effective medical care for CAD patients depends on availability and application of endovascular methods for CAD treatment. Percutaneous coronary intervention (PCI) using drug- eluting stents allows to achieve good clinical results even in most severe patients. The issues of personalized invasive treatment for patients with chronic coronary syndrome and optimal prevention of recurrent clinical events in survivors of acute coronary syndrome and PCI remain relevant.One of most important and unresolved problems in the pathophysiology of CAD is assessment of the nature of the inflammatory reaction that develops in the coronary vessels and myocardium in response to ischemic damage and PCI. Clinical studies focused on exploring correlation between the pro-inflammatory parameters of the patient’s status and the rate of secondary adverse events and aimed at revealing triggers of systemic and local inflammation are of great interest. Such a trigger could be the intestinal endotoxin (ET) which is capable of inducing systemic inflammation and, therefore, plays a significant role in the atherogenesis. A relationship between the endotoxin and cytokine system parameters should be investigated to develop a therapeutic concept for supporting CAD patients, including individuals after PCI. Parameters of systemic endotoxemia could be used as additional factors  in developing the biomarker-based approach to identify patients with active inflammation or fibrosis. This could result in development of specific therapy aimed at suppressing pro-inflammatory mediators and protecting the heart from inflammation.